Stability of ammonia oxidizer communities upon nitrogen fertilizer pulse disturbances is dependent on diversity - Mitsuta, Akari; Ishige, Nao; Tatsumi, Chikae; Madegwa, Yvonne Musavi; Kuramae, Eiko Eurya; Uchida, Yoshitaka (Elsevier BV, 2023)
Diversity of the soil microbial community is an important factor affecting its stability against disturbance. However, the impact of the decline in soil microbial diversity on the stability of ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) is not known, particularly considering the repeated soil nutrient disturbances occurring in modern agricultural systems. Here, we conducted a microcosm experiment and modified the soil microbial diversity using the dilution-to-extinction approach to determine the stability and population dynamics of AOB and AOA communities with repeated nitrogen (N) fertilizer application. Our results demonstrated that the AOB community became more abundant and stable against repeated disturbances by N in the treatments with the highest microbial diversity. In contrast, the abundance of AOA decreased following repeated N fertilizer application, regardless of the microbial diversity. Notably, during the initial application phase, AOA displayed a potential for increased abundance in treatments with high soil microbial diversity. These findings highlight that the soil microbial diversity controls the stability of ammonia oxidizers during shortinterval repeated N disturbances.
Keywords: Ammonia fertilizer; Ammonia-oxidizing archaea; Ammonia-oxidizing bacteria; Microbial community stability; Repeated disturbance; Soil microbial diversity; Soil Science; SDG 2 - Zero Hunger